Ng#-Irresolvable and Strongly Ng#-Irresolvable Spaces in Neutrosophic Topological Spaces - Martina Jency J.; Babisha Julit R. L.; Pious Missier S. (Neutrosophic Sets and Systems)
The notion of breaking down a topological space into smaller, disjoint subsets is the basis for the topological concepts of ‘resolvable space’ and ‘irresolvable space’. By synergizing topology and neutrosophy, we have introduced a new paradigm in neutrosophic topological spaces, represented by Ng#-resolvable spaces, Ng#-irresolvable spaces and strongly Ng#-irresolvable spaces. This pioneering fusion enables the exploration of novel mathematical structures and their characterizations.